Extractions in orthodontics: a treatment time evaluation and a profile susceptibility study - Junqueira, Cintia Helena Zingaretti (2016)
Able to significantly help in some malocclusions treatment, premolar extractions for orthodontic reasons has been extensively researched. The present thesis evaluated different aspects related to this type of extraction. The first study aimed to evaluate treatment duration of cases treated with four first premolars extraction, with and without dental crowding. After evaluating 150 Angle Class I malocclusion cases treated likewise, 74 selected individuals were divided into groups with mild and severe crowding. Although the treatment time was higher in the mild crowding group, that difference only became statistically significant difference after the groups were reselection of with more extreme crowding amounts. To achieve that, the groups were reduced. It is suggested this research should be repeated with a greater sample. The second study, through a certain type of article a systematic review of the literature was based on the common concern from orthodontists that their treatment could impact patients soft tissue profiles, especially treatments based on extractions. Lips projection and nasolabial angle values obtained from attractive samples were gathered. Results varied according to ethnicity and sex, showing that each patient must be evaluated considering the context he/she is inserted in. The orthodontic patients who show cephalometric values of lips projection and nasolabial angle similar to those reported in this study and are considered already attractive should be treated not changing the lips position.